Effect of increased body weight and obesity on the incidence of gynecological pathology, during childbirth, postnatal period and the state of newborns - L Yu Karakhalis; M N Mogilina (IP Berlin A.V., 2016)
Increased body weight and obesity affect the incidence of gynecological diseases, the development of children, the growth of estrogen-dependent diseases. The issues of prevention of obstetric complications in women with overweight and obesity through the use of modern desogestrel-containing contraceptives.